An `Expanded Equation' Approach to Weak-Exogeneity Tests in Structural Systems and a Monetary Application - Revankar, Nagesh S.; Yoshino, Naoyuki (The Review of Economics and Statistics, 1990)
Nagesh S. Revankar, Naoyuki Yoshino, An `Expanded Equation' Approach to Weak-Exogeneity Tests in Structural Systems and a Monetary Application, The Review of Economics and Statistics, Vol. 72, No. 1 (Feb., 1990), pp. 173-177